Discovery of Fungus-Derived Nornidulin as a Novel TMEM16A Inhibitor: A Potential Therapy to Inhibit Mucus Secretion in Asthma - Pongkorpsakol P; Yimnual C; Satianrapapong W; Worakajit N; Kaewin S; Saetang P; Rukachaisirikul V; Muanprasat C (Dove Medical Press, 2023)
Pawin Pongkorpsakol,1,* Chantapol Yimnual,2,* Wilasinee Satianrapapong,3 Nichakorn Worakajit,4 Suchada Kaewin,2 Praphatsorn Saetang,5 Vatcharin Rukachaisirikul,5 Chatchai Muanprasat2 1Princess Srisavangavadhana College of Medicine, Chulabhorn Royal Academy, Bangkok, Thailand; 2Chakri Naruebodindra Medical Institute, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Samut Prakan, Thailand; 3Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 4Program in Translational Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 5Division of Physical Science and Center of Excellence for Innovation in Chemistry, Faculty of Science, Prince of Songkla University, Songkhla, Thailand*These authors contributed equally to this workCorrespondence: Chatchai Muanprasat, Chakri Naruebodindra Medical Institute, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Samut Prakan, Thailand, Tel +66-85-2949658, Email chatchai.mua@mahidol.ac.thIntroduction: Inhibition of Ca2+-activated transmembrane protein 16A (TMEM16A) Cl− channels has been proposed to alleviate mucus secretion in asthma. In this study, we identified a novel class of TMEM16A inhibitors from natural sources in airway epithelial Calu-3 cells and determine anti-asthmatic efficacy of the most potent candidate in a mouse model of asthma.Methods: For electrophysiological analyses, IL-4-primed Calu-3 cell monolayers were mounted in Ussing chamber and treated with various fungus-derived depsidones prior to the addition of UTP, ionomycin, thapsigargin, or Eact to stimulate TMEM16A Cl− current. Ca2+-induced mucus secretion in Calu-3 cell monolayers was assessed by determining MUC5AC protein remaining in the cells using immunofluorescence staining. OVA-induced female BALB/c mice was used as an animal model of asthma. After the course of induction, cellular and mucus components in bronchoalveolar lavage were analyzed. Lungs were fixed and undergone with H&E and PAS staining for the evaluation of airway inflammation and mucus production, respectively.Results: The screening of fungus-derived depsidones revealed that nornidulin completely abolished the UTP-activated TMEM16A current in Calu-3 cell monolayers with the IC50 and a maximal effect being at ~0.8 μM and 10 μM, respectively. Neither cell viability nor barrier function was affected by nornidulin. Mechanistically, nornidulin (10 μM) suppressed Cl− currents induced by ionomycin (a Ca2+-specific ionophore), thapsigargin (an inhibitor of the endoplasmic reticulum Ca2+ ATPase), and Eact (a putative TMEM16A activator) without interfering with intracellular Ca2+ ([Ca2+]i) levels. These results suggest that nornidulin exerts its effect without changing [Ca2+]i, possibly through direct effect on TMEM16A. Interestingly, nornidulin (at 10 μM) reduced Ca2+-dependent mucus release in the Calu-3 cell monolayers. In addition, nornidulin (20 mg/kg) inhibited bronchoalveolar mucus secretion without impeding airway inflammation in ovalbumin-induced asthmatic mice.Discussion and Conclusion: Our study revealed that nornidulin is a novel TMEM16A inhibitor that suppresses mucus secretion without compromising immunologic activity. Further development of nornidulin may provide a new remedy for asthma or other diseases associated with allergic mucus hypersecretion without causing opportunistic infections.Keywords: TMEM16a, nornidulin, asthma, mucus secretion, airway epithelium